Zeremoniell als höfische Ästhetik in Spätmittelalter und Früher Neuzeit - Berns, Jörg Jochen,Rahn, Thomas,Berns, J Rg Jochen,Berns, Jorg Jochen (De Gruyter, 1995)
This volume assembles the papers presented at an international interdisciplinary symposium at the University of Marburg in early 1993. The 28 contributors marshal an extensive range of historical examples with a view to providing broad surveys and theoretical discussion of the way in which prescribed ceremonial etiquette and ceremonial practice can be drawn upon to delineate the aesthetics of courtly (also ecclesiastical and urban) culture. Reference is made to various aspects of the history of art, literature, theatre, science and the church.
Description based on publisher supplied metadata and other sources
Keywords: Kongress; Hofzeremoniell